DAMPAK LGBT DAN ANTISIPASINYA DI MASYARAKAT - M Ihsan Dacholfany (Nizham Jurnal Studi Keislaman, 2016)
This research discuss about the impact of LBT and its anticipation. LGBT has many impacts. The health impact can be shown by 78% homosexuals infected with sexually transmitted diseases. LBGT also provide social impact. The research shown that a gay have 20-106 couple per year. Whereas, someone zina’s couple is not more than 8 peoples in his whole life. 43% of gay groups who has investigated declare that in their whole life they do homosexual more than 500 people. In education impact, the learners who believe they are homo faced dropout problem 5 times greater than normal students because they feel insecurity. Moreover, 28% of them were force to leave the school. In the field of safety impact, homosexuals cause sexual abuse of children in United States; in fact their population just 2% of the total of America population. It can be concluded that 1 of 20 homosexual case is sexual abuse of children, whereas from 490 cases of adultery, one of that is the sexual abuse of children.